Application of the Collision Cell (CCT) in the ICP-MS Analytical System - Széles, Éva; Kovács, Béla; Prokisch, József; Győri, Zoltán (Acta Agraria Debreceniensis, 2005)
Our laboratory has seen a sharp rise in the number of requests for the analysis of smaller and smaller concentrations of elements from foods, plants, soil, organic fertiliser, irrigation and ground water, sewage, sewage sludge, raw material of food, as well as human and animal origin samples. From the above elements the inductively coupled plasma mass spectrometer is capable of analysing the smallest concentration of elements. Our method of analysis is to use our ICP-MS instrument, together with a ICP-MS with Collision Cell Technology (CCT). The CCT method has better detection limit, with 1-3 magnitudes, compared to the normal ICP-MS analytical method. The CCT has better detection limits mainly for the following elements in the periodical system: analysis of arsenic, selenium, germanium, vanadium and chromium. Additionally a collision cell can be applied for the analysis of silicium, sulphur, zink, copper, iron, calcium, magnesium and potassium in smaller concentrations.